Effects of transcranial magnetic stimulation combined with extracorporeal shockwave therapy for poststroke spasticity: study protocol for a randomised controlled trial - Man Yang; Lu Liu; Peng-Yu Wang; Yang Zhu; Ling-Yi Liao; Qiu-Yi Peng; Yong Tao; Jin-Jing Liu; Xiang-Qin Fang; Shi-Hao Gao; Chang-Yue Gao (BMJ Open)
Introduction Spasticity is a common complication of stroke, which is related to poor motor recovery and limitations in the performance of activities. Both transcranial magnetic stimulation (TMS) and extracorporeal shockwave therapy (ESWT) are effective treatment methods for poststroke spasticity (PSS). However, there is no existing study exploring the safety and effectiveness of TMS combined with ESWT for PSS.Methods and analysis This study will be a prospective, single-centre, randomised, factorial, controlled clinical trial. In this trial, 136 patients with PSS will be randomly divided into 4 groups: experimental group 1 (TMS), experimental group 2 (ESWT), experimental group 3 (ESWT+TMS) and control group, 34 patients in each group; all patients received routine rehabilitation. Outcome measures will be assessed by 4 time points: baseline (T0), 2 weeks after initiation of treatment (T1), 4 weeks after initiation of treatment (T2) and follow-up (4 weeks after the end of treatment, T3). The primary outcome is the modified Ashworth scale at T2. The secondary outcomes include the modified Tardieu scale for the degree of spasticity, the Fugl-Meyer assessment scale and range of motion (ROM) for motor function, the stroke-specific quality of life scale (SS-QOL) and modified Barthel index for activities of life, cortical excitability measured by TMS–surface electromyography (EMG), cerebral cortex oxygen concentrations measured by functional near-infrared spectroscopy (fNIRS) and Hmax/Mmax ratio measured by EMG.Ethics and dissemination This study protocol was approved by the Ethics Committee of the Army Medical Center of PLA (Approval No. 2024-04) on 24 January 2024. The study will be disseminated through peer-reviewed publications and conference presentations.Trial registration number This study was registered in the Chinese Clinical Trial Registry (https://www.chictr.org.cn/; unique identifier: ChiCTR2400080862; data: 9 February 2024; study protocol V. 2.0).